2008 IEEE Spoken Language Technology Workshop 2008
DOI: 10.1109/slt.2008.4777847
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of grammatical errors in non-native speech in english

Abstract: While a wide variety of grammatical mistakes may be observed in the speech of non-native speakers, the types and frequencies of these mistakes are not random. Certain parts of speech, for example, have been shown to be especially problematic for Japanese learners of English [1]. Modelling these errors can potentially enhance the performance of computer-assisted language learning systems.This paper presents an automatic method to estimate an error model from a non-native English corpus, focusing on articles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
1
22
0
1
Order By: Relevance
“…[25] trains a maximum entropy model using lexical and POS features to recognize a variety of errors. Their evaluation data partially overlaps with that of [24] and our paper.…”
Section: Related Workmentioning
confidence: 63%
See 2 more Smart Citations
“…[25] trains a maximum entropy model using lexical and POS features to recognize a variety of errors. Their evaluation data partially overlaps with that of [24] and our paper.…”
Section: Related Workmentioning
confidence: 63%
“…The work that is closely related to ours is that of Lee's [24], a supervised method built on the basic approach of template-matching on parse trees. To improve recall, the author uses the observed tree patterns for a set of verb form usages, and to improve precision, he utilizes n-grams as filters.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyber users distribute messages mainly in English over cyberspace. Non-native English authors write in a systematic manner, and corpus of writings often depends on the first language of the writer [8], [9].…”
Section: Author's Native Language Identificationmentioning
confidence: 99%
“…In our research, we included characterbased lexical features used in [8], vocabulary richness features in [11], and word-length frequency features used in [13]. In total, we adopted 64 lexical features to discriminating authors with different native languages in our texts shown in Table 1.…”
Section: B Feature Extractionmentioning
confidence: 99%